Comparative Analysis of Clustering and Chain Based Routing Protocols for Wireless Sensor Networks: A Review - Gaganpreet Kaur (International Journal of Advanced Science and Technology, 2020)
Routing is a challenging issue in wireless sensor networks. The path followed by the packets depends upon the routing strategy used. The packets must follow energy efficient path. Hierarchical routing based protocols are analyzed in this paper. These routing protocols are divided into three categories: Clustering based, Chaining based and hybrid routing protocols. Clustering based protocols are compared by taking into account some critical parameters such as construction of clusters, no. of clusters, criteria used for selection of cluster head, type of transmission between cluster head and base station. LEACH is one of the famous clustering based protocols so main focus in this paper is on extensions of LEACH protocol and how these extensions have overcome the drawbacks of LEACH protocol. Chaining based protocols are compared by taking into account the parameters such as no. of chains, criteria used for selection of chain leader, frequency of selection of chain leader and type of transmission between chain leader and base station. Hybrid protocols are combination of clustering based protocols and chaining based protocols so these are compared based on the criteria employed for selection of chain leaders and cluster heads.